COMPOSITE PICTURES FOR STUDENTS’ VOCABULARY ACHIEVEMENT - Rica Fatmawati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
The aim of this article is to investigate whether there was a significant effect of using Composite Picture of eighth grade students’ vocabulary achievement at SMPN 13 Malang.